Business Feasibility Observation Of Sweet Dried Tomato Product By SWOT Analysis At Giripurno Village, Batu City - Suprianti, Lilik; Jariyah, Jariyah; Pudji W, Endang; Rizal, Reda (International Journal Of Community Service, 2023)
Tomato is one agricultural commodity from Batu City which is so abundant in number. Although the number of products is relatively high, the benefit earned by tomato farmers is still uncertain due to price fluctuation. The other problem is the characteristic of the tomato that easy to get rotten. This condition increases the risk of farmers to get loss. One alternative solution to minimize the risk is processing the tomato as a sweet-dried tomato. Conversely, The sweet dried tomato product is still less popular than the fruit cracker in Batu City. Through the community service program, we help local people to make Strengths, Weaknesses, Opportunities, and Threats (SWOT analysis) to see the prospect of sweet-dried tomatoes. We also recommended some strategies for developing the sweet-dried tomatoes business to the village authority.